Organofluorine chemistry: Difluoromethylene motifs spaced 1,3 to each other imparts facial polarity to a cyclohexane ring - Jones, Mathew J.; Callejo, Ricardo; Slawin, Alexandra M. Z.; Bühl, Michael; O'Hagan, David (Beilstein Journal of Organic Chemistry, 2016)
2,2-Dimethyl-5-phenyl-1,1,3,3-tetrafluororocyclohexane has been prepared and characterised as an example of a facially polarised cyclohexane containing 1,3 related CF2 groups. The dipolar nature of the ring arises from the axial orientation of two of the C–F bonds pointing in the same direction, and set by the chair conformation of the cyclohexane. This electrostatic profile is revealed experimentally both in the solid-state (X-ray) packing of the rings and by solution (NMR) in different solvents. A computationally derived electrostatic profile of this compound is consistent with a more electronegative and a more electropositive face of the cyclohexane ring. This placing of CF2 groups 1,3 to each other in a cyclohexane ring is introduced as a new design strategy which could be applicable to the preparation of polar hydrophobic cyclohexane motifs.
Keywords: aliphatic rings; C–F bond; cyclohexane conformation; difluoromethylene group; organofluorine chemistry

(untitled) - Liu, W.; Huang, X.; Cheng, M.-J.; Neilson, R. J.; Goddard, W. A., III; Groves, J. T. (Science, 2012)

(untitled) - O’Hagan, D. (Chem. Soc. Rev., 2008)

Modern Fluoroorganic Chemistry - Kirsch, P. (Wiley-VCH, 2004)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

Fluorine in Medicinal Chemistry and Chemical Biology - Ojima, I. (Wiley-Blackwell, 2009)

(untitled) - Boiko, V. N. (Beilstein J. Org. Chem., 2010)

(untitled) - Leroux, F.; Jeschke, P.; Schlosser, M. (Chem. Rev., 2005)

(untitled) - Kirsch, P.; Bremer, M. (ChemPhysChem, 2010)

(untitled) - Kirsch, P.; Binder, W.; Hahn, A.; Jährling, K.; Lenges, M.; Lietzau, L.; Maillard, D.; Meyer, V.; Poetsch, E.; Ruhl, A.; Unger, G.; Fröhlich, R. (Eur. J. Org. Chem., 2008)

(untitled) - Biffinger, J. C.; Kim, H. W.; DiMagno, S. G. (ChemBioChem, 2004)

(untitled) - Callejo, R.; Corr, M. J.; Yang, M.; Wang, M.; Cordes, D. B.; Slawin, A. M. Z.; O’Hagan, D. (Chem. – Eur. J., 2016)

(untitled) - Wang, Y.; Callejo, R.; Slawin, A. M. Z.; O’Hagan, D. (Beilstein J. Org. Chem., 2014)

(untitled) - Urbina-Blanco, C. A.; Skibinski, M.; O’Hagan, D.; Nolan, S. P. (Chem. Commun., 2013)

(untitled) - O’Hagan, D.; Wang, Y.; Skibinski, M.; Slawin, A. M. Z. (Pure Appl. Chem., 2012)

(untitled) - Papoušek, D.; Papoušková, Z.; Chong, D. P. (J. Phys. Chem., 1995)

(untitled) - Fox, G. L.; Schlegel, H. B. (J. Chem. Phys., 1990)

(untitled) - Kawai, H. (Jpn. J. Appl. Phys., 1969)

(untitled) - Wudarczyk, J.; Papamokos, G.; Margaritis, V.; Schollmeyer, D.; Hinkel, F.; Baumgarten, M.; Floudas, G.; Müllen, K. (Angew. Chem., Int. Ed., 2016)

(untitled) - Fang, Z.; Al-Maharik, N.; Slawin, A. M. Z.; Bühl, M.; O’Hagan, D. (Chem. Commun., 2016)

(untitled) - Durie, A. J.; Slawin, A. M. Z.; Lebl, T.; Kirsch, P.; O’Hagan, D. (Chem. Commun., 2012)

(untitled) - Keddie, N. S.; Slawin, A. M. Z.; Lebl, T.; Philp, D.; O'Hagan, D. (Nat. Chem., 2015)

(untitled) - Duhamel, P.; Leblond, B.; Poirer, J.-M. (J. Chem. Soc., Chem. Commun., 1993)

(untitled) - Singh, R. P.; Shreeve, J. M. (Synthesis, 2002)

(untitled) - Sondej, S. C.; Katzenellenbogen, J. A. (J. Org. Chem., 1986)

(untitled) - Eddy, N. A.; Kelly, C. B.; Mercadante, M. A.; Leadbeater, N. E.; Fenteany, G. (Org. Lett., 2012)

(untitled) - Smissman, E. E.; Diebold, J. L. (J. Org. Chem., 1968)

(untitled) - Singh, R. P.; Majumder, U.; Shreeve, J. M. (J. Org. Chem., 2001)

(untitled) - Asato, A. E.; Liu, R. S. H. (Tetrahedron Lett., 1986)

(untitled) - Durie, A. J.; Fujiwara, T.; Cormanich, R.; Bühl, M.; Slawin, A. M. Z.; O’Hagan, D. (Chem. – Eur. J., 2014)